Food Waste Endangers Us All : What Can We Do About It? - Gew, Lai Ti * (Reach Publishing Sdn Bhd, 2022)
Malaysia has a huge food waste challenge. It is a perpetual problem. Landfill operator, SWCorp Malaysia has reported that as much as up to 17,000 tonnes of food waste are recorded on a daily basis. Of 17000 tonnes of food waste, 4080 tonnes (24%) are avoidable waste, and 76% are unavoidable waste. Interestingly, only 2% of the respondents carry out composting in one of the recent food waste study conducted by SWCorp.